Young Children (0-8) and digital technology: A qualitative exploratory study across seven countries - Chaudron, Stephane (Publications Office of the European Union, 2015)
Despite the growing number of very young children who go online and who are using a wide range of technologies, little is known about children’s interactions with those technologies. This report presents a pilot qualitative study designed and implemented in collaboration with a selected group of academic partners in different European countries that aims at pioneering in Europe the exploration of young children and their families` experiences with new technologies. It presents its results and discuss the findings at cross-national level on how children between zero and eight engage with digital technologies such as smartphones, tablets, computers and games; how far parents mediate this engagement and their awareness on the risks-opportunities balance. The report concludes on recommendations to parents, industries and policymakers.